Bismuth(III)-catalyzed cascade condensation of alkynyl alcohols with terminal alkynes: a facile construction of propargyl cyclic ethers - Pratapure, Madhukar S.; Kontham, Ravindar (Tetrahedron Letters, 2023)
Herein, we report a Bi(OTf)3-catalyzed cascade condensation between alkynols (particularly pent-4-yn-1ols and hex-5-yn-1-ols) and terminal alkynes (aryl alkynes) to facile access to diverse propargyl cyclic ethers (2 alkynyl tetrahydrofurans and 2 alkynyl tetrahydropyrans). This simple and efficient cascade transformation proceeds through initial intramolecular hydroalkoxylation of alkynols to give corresponding cyclic enol ethers (via exo-dig or endo-dig mode of ring-closure) followed by hydroalkynylation. Costeffective, naturally abundant, green Lewis acid catalysis, ambient reaction conditions, short reaction times, good substrate scope, and high yields are salient features of this strategy.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Alkynyl alcohols; Bismuth catalysis; Cascade condensation; Propargyl cyclic ethers; Terminal alkynes